A crystal plasticity-based approach for creep-fatigue life prediction and damage evaluation in a nickel-based superalloy. (February 2021) - Li, Kai-Shang; Wang, Run-Zi; Yuan, Guang-Jian; Zhu, Shun-Peng; Zhang, Xian-Cheng; Tu, Shan-Tung; Miura, Hideo
Highlights: A crystal plasticity-based approach is implemented to predict creep-fatigue life. Creep and fatigue indicator parameters are introduced to describe damage evolution. A potential methodology for conservative creep-fatigue life evaluation was provided. Abstract: A numerical process based on crystal plasticity finite element (CPFE) was implemented to predict creep-fatigue crack initiation life. CPFE-based model can describe the macroscopic cyclic deformation and reveal grain-level damage mechanism. A new life prediction approach was then constructed by introducing fatigue and creep indicator parameters. Furthermore, a series of strain-controlled creep-fatigue tests in GH4169 superalloy at 650℃ were used to validate predicted accuracy of this model, where most of the data points lied within ±1.5 error band. Finally, a potential methodology for conservative creep-fatigue life evaluation was provided by flexible creep-fatigue damage summation rule in engineering applications.